Clean Air Act Dynamism and Disappointments: Lessons for Climate Legislation to Prompt Innovation and Discourage Inertia - William W. Buzbee (Washington University Journal of Law & Policy, 2010)
The Clean Air Act ("CAA") is a behemoth of a law, with hundreds of pages and numerous titles reflecting decades of amendments. The law, through its many complex and interacting provisions, seeks to address the myriad sources of air pollution with a concomitant complex array of potential regulators and responsive regulatory strategies. Versions of the CAA preceding the substantial 1990 amendments were criticized by some as unduly rigid command and control regulations. Some of those criticisms undoubtedly were accurate, but key provisions of the CAA actually offer diverse and arguably laudable strategies that balance desire for stability and knowable legal obligations with the need for innovation, change, and antidotes to regulatory inertia. Effective, innovative provisions, as well as those proven to be flawed, provide lessons for other environmental legislation, especially climate change legislation.It appears likely that any federal climate change legislation will utilize a cap-and-trade scheme. A cap-and-trade scheme limits aggregate emissions of greenhouse gases ("GHGs") on an annual declining basis, distributes emission allowances, and permits trading of emission allowances and offset credits. Such a market-based regime likely would be coupled with numerous mandates and incentives structured to produce a lower polluting and more energy-efficient economy. Such a bill would offer some promise of innovation and checking of inertial forces, but if the bill lacks key strategies or utilizes strategies similar to those that have proven to be ineffective, it may lose key pro-innovation and inertia-fighting factors. Most notably, ambivalence toward state roles and technology-forcing provisions may result in climate legislation that omits strategies and structures that have proven effective in the CAA. This Article reviews these key strategies offering CAA dynamism and reflects on the lessons these strategies provide for climate change legislation.
Keywords: Regulatory compliance; Environmental law; Acid rain; Global warming; United States. Environmental Protection Agency; United States. Clean Air Act; Air pollution control; Emissions trading; Environmental impact analysis; Federalism